A Comparative Analysis of Institutional Capacities for Implementing Disability Policies in East African Countries: Functions of National Councils for Disability - Akiko Yokoyama (Disability, CBR and Inclusive Development)
During the “African Decade of Persons with Disabilities (2000-2009)”, East African countries witnessed significant achievements, especially in the development of law, collection of statistics and in funding. However, many persons with disability are still marginalised from opportunities in education, healthcare and employment. Purpose: With the pre-supposition that the lack of institutional capacities for implementing disability policies is the one major stumbling-block which hinders widespread delivery of social services to persons with disabilities in low-income countries, this study makes a comparative analysis of institutional capacities in the disability sectors of Uganda, Kenya and Tanzania. Method: The research methods adopted were a literature survey and a field survey. The framework for analysis consists of: 1) capacities and functions of disability units in central governments, 2) relationships between central and local governments in the disability sector, and 3) relationships between governments and organisations of persons with disability (DPOs). Special attention is paid to the status, roles and functions of national councils for disability (NCDs), the independent statutory bodies recently established in each of the three countries, with clear authority and duties for the implementation of disability policies. The NCDs enable multi-sectoral stakeholders to be involved in the implementation of disability policies; therefore, positive relationships between the governments and DPOs are essential for the smooth functioning of the NCDs. Results: While the result of the field survey in Tanzania reveals several effective approaches for the smooth operation of the NCD, further study is needed to verify whether these approaches would be applicable to other East African countries such as Kenya and Uganda. doi 10.5463/DCID.v23i2.106